2020
DOI: 10.1002/ijfe.2259
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic determinants of credit risk: Evidence from the Eurozone

Abstract: We propose and estimate several models controlling for firm-specific information, to examine the relation of macroeconomic variables with the probability of default of firms in the Eurozone. The novelty of our approach consists in capturing the informational value of macroeconomic factors on credit default prediction by using data from firms spanning 11 European countries; our

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 59 publications
2
17
1
Order By: Relevance
“…Macroeconomic information improves the accuracy of models anticipating non-financial business credit default. These findings are supported by previous studies on Oman, Sri Lanka, Nigeria, and Zambia (Kharusi and Ada, 2018;Madhuhansi and Shantha, 2021;Carvalho et al, 2020). The present study confirms the positive and negative links between total gross external debt, GDP, and non-performing loans, emphasizing the importance of monitoring external debt levels for economic stability.…”
Section: Macroeconomic Cyclical Indicatorssupporting
confidence: 91%
“…Macroeconomic information improves the accuracy of models anticipating non-financial business credit default. These findings are supported by previous studies on Oman, Sri Lanka, Nigeria, and Zambia (Kharusi and Ada, 2018;Madhuhansi and Shantha, 2021;Carvalho et al, 2020). The present study confirms the positive and negative links between total gross external debt, GDP, and non-performing loans, emphasizing the importance of monitoring external debt levels for economic stability.…”
Section: Macroeconomic Cyclical Indicatorssupporting
confidence: 91%
“…The goal is to increase the understanding of underlying macroeconomic causes of credit risk and predict the macroeconomic variables to which credit risk is most sensitive with accuracy (high-and low-credit-risk zones). This will enable beneficiaries to deploy control mechanisms to prevent projected credit losses and maintain adequate reserves to comply with UK regulatory norms [4]. This section discusses the credit risk predictive model's development and comparison to select the most accurate model using measures like the confusion matrix and receiver operating characteristic curve (ROC).…”
Section: Discussionmentioning
confidence: 99%
“…The 2008 global crisis revealed the interwoven nature of banking and macroeconomic indicators such as unemployment, inflation, etc. Also, it showed that a negative shift in macroeconomic indicators such as the unemployment rate, inflation, GDP, etc., initiates a vicious cycle, causing financial stress in the ecosystem [4]. Since COVID-19, global financial circumstances have deteriorated and are becoming worse because of the Russia-Ukraine war.…”
Section: Introductionmentioning
confidence: 99%
“…Brunel [10] provided a comprehensive survey of PD analytics methodology. To explore the impact of GDP growth on PD, Carvalho et al [11] observed that with a negative effect on the PD, GDP growth is the most significant among the key macroeconomic predictors of default. However, they also report that reduced PD due to economic growth mostly occurs in economies more exposed to conditions of financial stress.…”
Section: Literature Reviewmentioning
confidence: 99%